Electronic Scientific Data & Literature Aggregation: A Review for Librarians. - Barbara Losoff (Issues in Science and Technology Librarianship)
The advent of large-scale digital repositories, along with the need for sharing useful data world-wide, demands change to the current information structure. The merging of digital scientific data with scholarly literature has the potential to fulfill the Semantic Web design principles. This paper will identify factors leading to integration of databases and journal literature; discuss the visions of the merged format proposed by scientists; and librarians' role in this transformation. [ABSTRACT FROM AUTHOR]